Direct recovery of scrapped LiFePO4 by a green and low-cost electrochemical re-lithiation method. Issue 16 (3rd August 2022) - Zhou, Shiyu; Du, Jingzhen; Xiong, Xiaosong; Liu, Lili; Wang, Jing; Fu, Lijun; Ye, Jilei; Chen, Yuhui; Wu, Yuping
Abstract : This study proposes a novel electrochemical method for recycling LFP based on a Zn//S-LFP double-electrode system, providing green and low-cost recycling technology for future industrial applications. Abstract : The extensive application in recent years of lithium-ion batteries (LIBs) based on an LiFePO4 (LFP) cathode in electric vehicles will lead to a large amount of scrapped LFP in the foreseeable future. Therefore, recycling these scrapped cathode materials appropriately will become an extremely important issue. Here, a facile and green method is developed to directly regenerate scrapped LFP into a fresh cathode. We propose a re-lithiation approach that intercalates lithium ions into scrapped LFP in an aqueous solution system. Specifically, the configuration of the recycling device is a H-type electrolytic bath, in which the cathode and anode electrolytes are separated by an anion-exchange membrane, a zinc plate is used as the anode, the scrapped LFP suspension is regarded as the cathode, and the electrolyte is lithium salt aqueous solution. The regenerated LFP is obtained via a discharging process. It is found that the effectiveness of the recycling process is directly related to the parameters of the discharge current (mA) and theoretical intercalation amount of lithium (TIA). The results show that the performance of LFP recycled at a current of 5 mA and 150%-TIA is the best; it has high lithium content and better crystallinity, and it also exhibits excellent electrochemical performance with a high discharge capacity of 134.0 mA h g −1 at 1C and a capacity retention rate of 85.5% after 300 cycles. Furthermore, we adopt FTIR spectroscopy to assess the quality of the regenerated LFP intuitively and simply, thus providing a feasible monitoring standard for industrial production.